APPLICATION OF THE REFLECTIVE LEARNING THEORY IN DISCLOSURE OF STUDENT ACHIEVEMENTS WHEN LEARNING GRAMMAR II IN IAIN LANGSA. - Hasbalnikistan, Muhammad Yusuf; Mahriza, Rita; Muslem (JL3T (Journal of Linguistics, Literature and Language Teaching), 2019)
The objective of this study is to find out what are the reflection of students’ achievement after learning sentences structure grammar II at IAIN Langsa.Reflection represents serious consideration of past actions and experiences with the aim to evaluate them for future actions. This research was qualitative that conducted in one class. The data has been taken by questionnaires and interviews. It is a descriptive survey research including questionnaires and interview. After collecting the data, they were analyzed and described to have the final results. The result of this thesis illustrates that there are several students’ achievement reflections after learning grammar II at IAIN Langsa. There such the awareness of students of independent learning and the awareness of students about the role of students in solving a problem.